Antioxidant mitoquinone ameliorates EtOH-LPS induced lung injury by inhibiting mitophagy and NLRP3 inflammasome activation - Sang, Wenhua; Chen, Sha; Lin, Lidan; Wang, Nan; Kong, Xiaoxia; Ye, Jinyan (Frontiers in Immunology, 2022)
Chronic ethanol abuse is a systemic disorder and a risk factor for acute respiratory distress syndrome (ARDS) and chronic obstructive pulmonary disease (COPD). However, the mechanisms involved are unknown. One explanation is that ethanol produces damaging reactive oxygen species (ROS) and disturb the balance of mitochondria within the lungs to promote a pro-injury environment. We hypothesized that targeting an antioxidant to the mitochondria would prevent oxidative damage and attenuate EtOH-LPS-induced lung injury. To test this, we investigated the effects of mitochondria-targeted ubiquinone, MitoQ on ethanol-sensitized lung injury induced by LPS. Lung inflammation, ROS, mitochondria function and mitophagy were assessed. We demonstrated that chronic ethanol feeding sensitized the lung to LPS-induced lung injury with significantly increased reactive oxygen species ROS level and mitochondrial injury as well as lung cellular NLRP3 inflammasome activation. These deleterious effects were attenuated by MitoQ administration in mice. The protective effects of MitoQ are associated with decreased cellular mitophagy and NLRP3 inflammasome activation in vivo and in vitro. Taken together, our results demonstrated that ethanol aggravated LPS-induced lung injury, and antioxidant MitoQ protects from EtOH-LPS-induced lung injury, probably through reducing mitophagy and protect mitochondria, followed by NLRP3 inflammasome activation. These results will provide the prevention and treatment of ethanol intake effects with new ideas.